5SQUAL: Uma ferramenta baseada no modelo 5S para avaliação de qualidade em bibliotecas digitais - Barbara Lagoeiro Moreira (2007)
Digital libraries (DLs) are complex information systems which can present changes in their structures, content, and services over time. These complexity and dynamics makes the system maintaining task something not trivial, as it requires periodical evaluations of the DL different components. Generally, these evaluations are customized per system and are done as problems happen in the DL and the administrator intervention is required. This work aims to change this figure, presenting 5SQual, a tool which provides ways to perform automatic and configurable evaluations of digital objects, metadata, and services of a DL. The tool implements diverse numeric indicators that are associated to 8 dimensions described in the 5S quality model. Its architecture was developed aiming its applicability in various DLs. Among the contributions of this work, we can highlight the implementation and evaluation (with usability specialists) of a graphical interface to guide the configuration of 5SQual evaluations and an interview about the expectations on 5SQual that was done with administrators of real DLs.